Comparative efficacy of five most common traditional Chinese medicine monomers for promoting recovery of motor function in rats with blunt spinal cord injury: a network meta-analysis - Xu, Luchun; Yang, Yongdong; Zhong, Wenqing; Li, Wenhao; Liu, Chen; Guo, Ziwei; Yu, Xing (Frontiers in Neurology, 2023)
Objective This research employed a network meta-analysis (NMA) to examine the effectiveness of five traditional Chinese medicine (TCM) monomers for promoting motor function recovery in rats with blunt spinal cord injury (SCI). Methods Wangfang, China National Knowledge Infrastructure, Web of Science, Embase, Chinese Scientific Journal Database, PubMed, and the Chinese Biomedical Literature Databases were searched for retrieving relevant articles published from their inception to December 2022. Two reviewers performed screening of search results, data extraction, and literature quality assessment independently. Results For this meta-analysis, 59 publications were included. Based on the recovery of motor function at weeks 1, 2, 3, and 4 in NMA, almost all TCM groups had significantly increased positive effects than the negative control animals. In terms of cumulative probability, the tanshinone IIA (TIIA) group ranked first in restoring motor function in the first week after blunt SCI, and the resveratrol (RSV) group ranked first during the last 3 weeks. Conclusion The NMA revealed that TCM monomers could effectively restore motor function in the rat model of blunt SCI. In rats with blunt SCI, TIIA may be the most effective TCM monomer during the first week, whereas RSV may be the most effective TCM monomer during the last 3 weeks in promoting motor function recovery. For better evidence reliability in preclinical investigations and safer extrapolation of those findings into clinical settings, further research standardizing the implementation and reporting of animal experiments is required. Systematic Review Registration https://inplasy.com/, identifier INPLASY202310070.